2019
DOI: 10.1002/pcr2.10088
|View full text |Cite
|
Sign up to set email alerts
|

Studies on why the heat deflection temperature of polylactide bioplastic cannot be improved by overcrosslinking

Abstract: The high temperature application of polylactide (PLA) has been greatly limited by its low heat deflection temperature (HDT). As a slow crystallizing material, the HDT of amorphous PLA is mainly determined by its low T g value, near 55°C. In this work, PLA was chemically crosslinked, and the HDT of the crosslinked PLA was evaluated from two aspects—crystallization ability improvement and chain mobility limitation at T g of the PLA. The crystallization rate is improved by crosslinking because of the increased nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…The list of mean HDT values obtained for PLA and its composites is presented in Figure 11 . According to Wu et al, the possibility of improving HDT due to the partial crosslinking of the PLA structure as an effect of interactions with CE bonded to filler may be neglected [ 66 ]. An increase in HDT value in PLA is usually associated with an increased share of the crystalline phase [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…The list of mean HDT values obtained for PLA and its composites is presented in Figure 11 . According to Wu et al, the possibility of improving HDT due to the partial crosslinking of the PLA structure as an effect of interactions with CE bonded to filler may be neglected [ 66 ]. An increase in HDT value in PLA is usually associated with an increased share of the crystalline phase [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to compounds such as SAGM, which are functionalized with oligomers, peroxides or isocyanates are also used. However, problems with the proper dosing of many compounds and the possibility of blend structure cross-linking [28] make chain extenders gain popularity as effective compatibilizers. Reactive CE compatibilizers significantly improve the toughness and elongation at the break of the PLA-based blends, which was already confirmed by many studies [18,[29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that PLA, the polymer matrix employed in this FDM process, has a deflection temperature (HDT) near 55 • C [52,53]. HDT is a measure of the resistance of a polymer to deformation (stiffness of material) when subjected to stress loading at elevated temperatures.…”
Section: Discussionmentioning
confidence: 99%